PADANAN PARTIKEL AKHIR-KALIMAT (SHUUJOSHI) NA(A) DALAM KOMIK DETECTIVE CONAN VOLUME 8 - Sinta Arisnawati; Nana Rahayu; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study describes the equivalent of final sentence particle (shuujoshi) na(a) studied in the Detective Conan comic volume 8. The problem in this study is to find out what the equivalence of na(a) in the comic. The purpose of this study is to explain what are the results of the equivalent na(a) studied in the comic. This study uses a qualitative descriptive method of the functions na(a) in a sentence or conversation. The results are divided into 2 types of data, namely na(a) which has a translation equivalent and na(a) that has no translation equivalent.Key Words: Detective Conan, comic, final sentence particles, equivalent.